Examining Cambodian EFL University Learners’ Perceived Autonomy, Engagement, and Performance - Somara Sun (Journal of General Education and Humanities, 2025)
Despite studies highlighting the importance of learner autonomy, engagement, and academic performance in various contexts, the research gap in Cambodian EFL instruction is significant. This study compared Cambodian EFL university students' perceptions of learner autonomy, learner engagement, and academic performance based on gender, study level, and university type. A quantitative method was applied, involving cluster sampling and a bilingual questionnaire in English and Khmer. Data from 108 participants—selected randomly from 2nd, 3rd, and 4th-year students at three universities in Phnom Penh—was analyzed using SPSS (Version 23) with descriptive and inferential statistics. Findings revealed that public university students exhibit much higher learner autonomy than their private university counterparts, although both groups demonstrate equal levels of engagement and academic performance. Gender and university type influenced perceptions of autonomy, with male students and those from certain universities perceiving greater autonomy. In conclusion, this study filled a research gap in Cambodian EFL instruction by comparing university students' perceptions of learner autonomy, engagement, and academic performance. The study underscores the necessity of targeted interventions to address gender disparities in autonomy and engagement, emphasizing the need for inclusive educational strategies for female students.